2021
DOI: 10.1093/brain/awaa458
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical anterior optic pathway involvement in early multiple sclerosis and clinically isolated syndromes

Abstract: Optical coherence tomography (OCT) is gaining increasing relevance in the assessment of patients with multiple sclerosis. Converging evidence point to the view that neuro-retinal changes, in eyes without acute optic neuritis, reflect inflammatory and neurodegenerative processes taking place throughout the CNS. The present study aims at exploring the usefulness of OCT as a marker of inflammation and disease burden in the earliest phases of the disease. Thus, a cohort of 150 consecutive patients underwent clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
5
20
3
Order By: Relevance
“…Furthermore, progressive thinning of the retinal ganglion cell (RGC) and the inner plexiform layer has also been described for relapsing–remitting MS (RRMS) [ 29 ]. This more recent data is consistent with previous literature showing continuous RNFL thinning in CIS and MS patients with and without ON [ 14 , 30 , 31 ]. These findings are consistent with post-mortem analysis of MS patients, showing RNFL, GCL, and INL thinning [ 32 ].…”
Section: Optical Coherence Tomographysupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, progressive thinning of the retinal ganglion cell (RGC) and the inner plexiform layer has also been described for relapsing–remitting MS (RRMS) [ 29 ]. This more recent data is consistent with previous literature showing continuous RNFL thinning in CIS and MS patients with and without ON [ 14 , 30 , 31 ]. These findings are consistent with post-mortem analysis of MS patients, showing RNFL, GCL, and INL thinning [ 32 ].…”
Section: Optical Coherence Tomographysupporting
confidence: 93%
“…Within 1 year after the episode, INL levels return to baseline level. INL thickness is therefore discussed as a marker of acute inflammatory activity [ 13 , 14 ]. INL thickening is further associated with the extent of ganglion cell loss after acute ON.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that α-syn triggers neuroinflammation, and that, in turn, inflammation increases α-syn phosphorylation and pathology in synucleinopathies ( Lee et al, 2010 ; Tansey and Goldberg, 2010 ; Ramirez et al, 2017 ; Ferreira and Romero-Ramos, 2018 ). Furthermore, retinal inflammation has been linked to both swelling of the outer retina and ERG deviations, and may therefore underlie -at least in part- the OCT and ERG abnormalities that we observed in the Thy1-h[A30P]α-syn mice ( Mirza and Jampol, 2013 ; Petzold, 2016 ; Pisa et al, 2021 ; Xia et al, 2021 ). Hence, we next investigated macroglia and microglia reactivity and water homeostasis in the retina.…”
Section: Resultsmentioning
confidence: 95%